2011
DOI: 10.14499/indonesianjcanchemoprev2iss1pp182-186
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity Assay From Fractions of Hedyotis corymbosa Extract Against Breast Cancer Cell Line T47D

Abstract: Drug discovery for cancer medication is the most important effort that researcher do at this time. Indonesia bio diversities have possibility as a cancer medicine sources. Finding a herbal medicine for cancer treatment is a first step to find a right cancer medicine in the future. This research has already completed for the earlier another research. Some fractions of Hedyotis corymbosa extract has been analyzed using Sulforhodamine B method with UV wavelength 515 nm against T47D cell line, a human breast cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…After fractionation, the methylene fraction exhibits an IC 50 of 2.75 µg/mL. Our ethanol extract and its fraction in nhexane, methylene chloride, and ethyl acetate have been previously reported to be inhibitory to breast cancer T47D cell line [13], with IC 50 of 9.63, 33.45, 54.59 and 52.58 µg/mL, respectively.…”
Section: Assay For Cytotoxic Activitymentioning
confidence: 72%
See 2 more Smart Citations
“…After fractionation, the methylene fraction exhibits an IC 50 of 2.75 µg/mL. Our ethanol extract and its fraction in nhexane, methylene chloride, and ethyl acetate have been previously reported to be inhibitory to breast cancer T47D cell line [13], with IC 50 of 9.63, 33.45, 54.59 and 52.58 µg/mL, respectively.…”
Section: Assay For Cytotoxic Activitymentioning
confidence: 72%
“…Methine carbons at δ C 93.4 and 100.1 expected to have deshielding effect and suggested to be linked with two oxygen atom. By exposure of 13 C NMR, we suggested that it has monoterpene and glucopyranosyl basic skeleton. The basic skeleton of monoterpene was from ten carbon of one methylene sp , and one carbonyl (C=O).…”
Section: Assay For Cytotoxic Activitymentioning
confidence: 92%
See 1 more Smart Citation
“…This phenomenon occurs due to its major compound, ursolic acid, has been known to exhibit cytotoxic effect after 48 hours of treatment (Harmand, et al, 2005;Li, et al, 2010). Several previous reports also have been revealed that Hedyotis corymbosa L. exhibited cytotoxic effect on cancer cell lines, including K562 cells, WiDr cells, COLO 205 cells, Hep3B cells, H460 cells, also on T47D and MCF-7 breast cancer cells (Pandey, et al, 2012;Meiftasari, et al, 2016;Lee, et al, 2011;Andriyani, et al, 2011;Haryanti, et al, 2009). According to study by Endrini (2011), the cytotoxic effect from Hedyotis corymbosa L. was associated with high antioxidant activities from flavonoid and phenolic compounds in extract.…”
Section: Discussionmentioning
confidence: 97%
“…extract, Previous study reported that Hedyotis corymbosa L. ethanolic extract showed significant anticancer activity on K562 human leukemia cell lines (Pandey, et al, 2012) and on WiDr colon cancer (Meiftasari, et al, 2016). Moreover, its ethanolic extract also revealed its cytotoxic effect on MCF-7 and T47D breast cancer cells with IC 50 value of 77 µg/mL and 62 µg/mL, respectively (Haryanti, et al, 2009;Andriyani, et al, 2011). However, no study has been done to evaluate the cytotoxic effect of the extract towards metastatic cancer cells.…”
Section: Introductionmentioning
confidence: 98%